The Alzheimer’s Amyloid-β(1–42) Peptide Forms Off-Pathway Oligomers and Fibrils that are Distinguished Structurally by Intermolecular Organization - Tay, William M. (J Mol Biol, 2013)
Increasing evidence suggests that soluble aggregates of amyloid-β (Aβ) initiate the neurotoxicity that eventually leads to dementia in Alzheimer’s disease. Knowledge of soluble aggregate structures will enhance our understanding of the relationship between structures and toxicities. Our group has reported a stable and homogeneous preparation of Aβ(1–42) oligomers that has been characterized by various biophysical techniques. Here, we have further analyzed this species by solid state nuclear magnetic resonance (NMR) spectroscopy and compared NMR results to similar observations on amyloid fibrils. NMR experiments on Aβ(1–42) oligomers reveal chemical shifts of labeled residues that are indicative of β-strand secondary structure. Results from 2D DARR experiments indicate proximities between I31 aliphatic and F19 aromatic carbons. An isotope dilution experiment further indicates that these contacts between F19 and I31 are intermolecular, contrary to models of Aβ oligomers proposed previously by others. For Aβ(1–42) fibrils we observed similar NMR lineshapes and inter-sidechain contacts, indicating similar secondary and quaternary structures. The most prominent structural differences between Aβ(1–42) oligomers and fibrils were observed through measurements of inter-molecular (13)C-(13)C dipolar couplings observed in PITHIRDS-CT experiments. PITHIRDS-CT data indicate that, unlike fibrils, oligomers are not characterized by in-register parallel β-sheets. Structural similarities and differences between Aβ(1–42) oligomers and fibrils suggest that folded β-strand peptide conformations form early in the course of self-assembly, and that oligomers and fibrils differ primarily in schemes of inter-molecular organization. Distinct inter-molecular arrangements between Aβ(1–42) oligomers and fibrils may explain why this oligomeric state appears off-pathway for monomer self-assembly to fibrils.